Incremento das vendas do comércio de Santana do Livramento em função da flutuação cambial: estudo de caso no supermercado Niederauer - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This research aims to identify the contribution of the exchange rate fluctuation in the increase of sales in Santana do Livramento from the Niederauer Supermarket. To develop the present research the case study method was used, through which the supermarket was analyzed based on the perception of its employees. The research technique used was descriptive, with qualitative bias, and the instrument used was to collect data from questionnaires with semistructured interviews and content analysis. The results of the research analyzed show that the rise in foreign exchange, peso and dollar exchange rates, and floating exchange rates are the biggest incentives for foreigners to buy in Brazilian trades. These factors are positive points for both the supermarket and the frontier due to always having circulating currency in the trades, mainly in the Brazilian. The currency has the function as means of exchange: intermediary between the commodities; with unit of account: to be the reference of the exchanges, the instrument by which the commodities are quoted; and as a reserve of value: buying power that is maintained in time, a way of measuring wealth.
Increase in Santana do Livramento's sale in function of floating cambial change: case estudy in Niderauer supermarket
Keywords: Câmbio flutuante; Taxa de câmbio; Comércio; Zona de fronteira; Floating currency exchange; Exchange rate; Trade; Border zone; CNPQ::CIENCIAS SOCIAIS APLICADAS